Efektivitas Fungsi DPRD dalam Mengawasi Pengelolaan APBD Kabupaten Gorontalo - Mohamad, Usman; Marwan, Marwan; Insani, Nur (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study examines the effectiveness of the Gorontalo Regency Regional People's Representative Council's (DPRD) oversight of the implementation of the Regional Budget (APBD), using normative and empirical legal methods. Regulatorily, the DPRD possesses formal oversight instruments such as the right of interpellation and working meeting mechanisms. Still, their implementation is often hampered by member capacity, limited resources, local government transparency, and the dominance of political interests. The results of the study indicate that strengthening DPRD capacity, executive transparency, and public participation are crucial to enhancing oversight effectiveness and achieving accountable and responsive regional governance.